Architectural and Structural Characteristics of Masonry Buildings between the 19th and 20th Centuries in Lisbon, Portugal - Simoes, Ana G. (2017)
The masonry buildings constructed between the 19th and 20th centuries in Lisbon are commonly recognized for their eclectic style and structural vulnerability. This article presents the main characteristics of these buildings in the aim of preserving their cultural value. The socio-economic conditions on what they were constructed are identified. This includes the possible reasons for the negative impression attributed to the buildings, which end up to be known as gaioleiro (meaning bird cage). The architectural features are described in terms of urban plan and aesthetics, configuration of the buildings and layout of the flats. The structural system and materials are characterized. In addition, an estimation of the mechanical properties of the materials is presented based on the Bayesian approach. The main weaknesses and alterations implemented are also identified, putting in evidence the possible consequences for the structure and seismic performance.